Professional Microsoft SQL server 2008 reporting services - Turley, Paul 1962- (Wrox professional guides, 2009)
Teaches solution architects, designers, and developers how to use Microsoft's reporting platform to create reporting and business intelligence (BI) solutionsUpdated with new information about holistic BI solutions, comprehensive OLAP/Analysis Services reporting, and complete production deployment scenariosIncludes programming examples focused on specific, scenario-based solutionsExplains reporting services architecture and business intelligence, teaches the fundamentals of designing reports through the use of careful planning considerations, and covers advanced report desig.